The effect of curing time by conventional quartz tungsten halogens and new light-emitting diodes light curing units on degree of conversion and microhardness of a nanohybrid resin composite - Tanthanuch, Saijai (J Conserv Dent, 2019)
BACKGROUND: Little is known about the relationship between the minimal light-curing time required for proper polymerization on various quartz–tungsten–halogen (QTH) and light-emitting diode (LED) light-curing units that have different light intensities. AIM: To evaluate the effects of curing time by QTH and LED light-curing units on the degree of conversion (DoC) and surface microhardness of a nanohybrid resin composite. SETTING AND DESIGN: Experimental design. MATERIALS AND METHODS: One hundred and twenty cylindrical specimens (4.0 mm in diameter, 2.0 mm thick) of shade A2 resin composite were prepared and polymerized with either QTHs or LEDs for 20 and 40 s. The DoC and the top and bottom surface microhardness were recorded. STATISTICAL ANALYSIS USED: Two-way analysis of variance, Tukey's test, and the t-test (α = 0.05) were used. RESULTS: Surface microhardness and DoC values were affected by light intensity and curing time (P < 0.05). In terms of microhardness and DoC, LED groups gave significantly more values than QTH groups (P < 0.05). CONCLUSION: Curing time affected surface microhardness and DoC values of a nanohybrid resin composite in both conventional QTH and new LED light-curing units.